2005
DOI: 10.1074/jbc.m508786200
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 and Microtubules Are Required for Autophagic Degradation of Aggregated Huntingtin

Abstract: CNS neurons are endowed with the ability to recover from cytotoxic insults associated with the accumulation of proteinaceous polyglutamine aggregates via a process that appears to involve capture and degradation of aggregates by autophagy. The ubiquitinproteasome system protects cells against proteotoxicity by degrading soluble monomeric misfolded aggregation-prone proteins but is ineffective against, and impaired by, non-native protein oligomers. Here we show that autophagy is induced in response to impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
620
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 655 publications
(651 citation statements)
references
References 66 publications
27
620
3
1
Order By: Relevance
“…EM revealed the presence of dark c-shaped structures in the cytoplasm, corresponding to late degradative autophagolysosomes ( Figure 4A). 23 Similar structures were occasionally seen in control mice but at a much lower abundance. Furthermore, enhanced mRNA levels of LC3 (P Ͻ 0.01), important in the formation of the autophagosomes, and a trend toward an increase in the ratio between phosphatidylethanolamine-conjugated LC3 (LC3-II) and LC3-I (P ϭ 0.10) confirmed this result ( Figure 4, B and C).…”
Section: Autophagy and Granule Abnormalities In Paneth Cells Of Starvmentioning
confidence: 58%
“…EM revealed the presence of dark c-shaped structures in the cytoplasm, corresponding to late degradative autophagolysosomes ( Figure 4A). 23 Similar structures were occasionally seen in control mice but at a much lower abundance. Furthermore, enhanced mRNA levels of LC3 (P Ͻ 0.01), important in the formation of the autophagosomes, and a trend toward an increase in the ratio between phosphatidylethanolamine-conjugated LC3 (LC3-II) and LC3-I (P ϭ 0.10) confirmed this result ( Figure 4, B and C).…”
Section: Autophagy and Granule Abnormalities In Paneth Cells Of Starvmentioning
confidence: 58%
“…It was also shown that phosphorylation of HDAC6, activating its deacetylase activity, promotes proper aggresome formation and protects from toxicity 50 . Indeed, HDAC6 inhibition would impair the removal of aggregated protein by retrograde transport to autophagosomes and lysosomes as it was shown that tubacin treatment decreased the recruitment of Atg/LC3, a crucial component of autophagic transport 51 , and that HDAC6 expression rescued neurodegeneration in a model of spinal and bulbar muscular atrophy 52 . HDAC6 has been shown also to protect dopaminergic neurons from alpha-synuclein-induced toxicity 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the preferential binding of kinesin-1 to acetylated a-tubulin is proposed to mediate the effect of HDAC6 inhibition on JIP1 transport. Likewise, the acetylation-dependent binding of kinesins or other molecular motors and microtubule-associated proteins to tubulin may provide an explanation for the reported effects of HDAC6 catalytic activity on the transport of protein aggregates to aggresomes (Kawaguchi et al, 2003), on the recruitment of the autophagic machinery to aggresomes (Iwata et al, 2005), on cell motility (Hubbert et al, 2002;Haggarty et al, 2003), on the organization of the immune synapse in T cells (Serrador et al, 2004) and on the polarized release of cytokine-containing secretory lysosomes (Carta et al, 2006).…”
Section: Deacetylase-dependent Functions Of Hdac6mentioning
confidence: 99%